The Effect of Socio-Scientific Issues Approach on Student Learning Outcomes in Physics Learning: A Review - Suryani, Yani; Anggraini, Welly (Jurnal Pijar Mipa, 2025)
The Socio-Scientific Issues (SSI) approach integrates social issues with scientific concepts to enhance the relevance of learning, including in the context of physics education. This study aims to systematically analyze the literature concerning the influence of the SSI approach on students’ learning outcomes in physics. The method employed is a Systematic Literature Review (SLR) guided by the PRISMA framework, which includes the stages of Identification, Screening, Eligibility, and Inclusion of articles published between 2020 and 2024 from the Google Scholar database. The data extracted from the selected articles were analyzed using a thematic analysis approach through manual coding, categorized into the domains of learning outcomes: cognitive, affective, and psychomotor. The analysis of 20 studies indicates that the implementation of SSI significantly improves students’ learning outcomes. Students exhibited deeper conceptual understanding, enhanced critical thinking skills, improved problem-solving abilities, increased scientific literacy, and more positive attitudes toward science. This study recommends the integration of the SSI approach into the physics curriculum to foster more contextualized and meaningful learning experiences.